Pengaruh Transparansi dan Akuntabilitas Publik Terhadap Kinerja Pelayanan pada Rumah Sakit Daerah Massenrempulu Kabupaten Enrekang - Iis Nurnatasyiah h; Djamali, Hisnio (Insan Cita Bongaya Research Journal, 2023)
This study aims to analyze the effect of transparency and public accountability on service performance at Massenrempulu Regional Hospital, Enrekang Regency. The sampling technique uses a simple random sampling method. The sample taken as respondents amounted to 64 employees. Data were collected using questionnaire techniques. The analysis method uses multiple linear regression. The results showed transparency and public accountability for service performance.